Assessing Hazards and Risks Associated in the Construction Projects: A Case Study of Akure, Nigeria - Albert, Idowu (Urban Planning and Construction, 2025)
The construction industry, a major contributor to national economic growth, faces significant challenges in ensuring occupational health and safety, particularly due to the increasing demand for infrastructure. This study investigates the hazards and risks associated with construction projects, focusing on their impact on workers and project outcomes. To accomplish this, the study identifies the hazards and risks associated with construction project, assesses the effects of the identified hazards and risks on construction workers and project outcomes, and strategies to reduce hazards and risks. A quantitative research approach was employed using structured questionnaires distributed to 135 built environment professionals in Akure, Nigeria. The findings reveal that slips and trips, electrical shocks, and being struck by moving machinery are the most significant hazards, while cost overruns, project delays, and fatigue from manual handling tasks are common consequences. Despite moderate awareness of these hazards, the implementation of effective safety measures remains inconsistent due to inadequate training, weak enforcement of regulations, and budgetary constraints. Strategies such as fostering a safety-first culture, regular hazard assessments, enhanced training, and stricter regulatory enforcement were identified to improve safety performance during production. The study concludes by emphasizing the urgent need for proactive, integrated risk management systems to minimize hazards and promote a safer construction environment in Nigeria.